Ultraviolet-B Radiation Represses Primary Root Elongation by Inhibiting Cell Proliferation in the Meristematic Zone of Arabidopsis Seedlings - Sheridan, Maria Luján; Simonelli, Lucio; Giustozzi, Marisol; Casati, Paula (Frontiers in Plant Science, 2022)
In Arabidopsis thaliana plants, exposure to UV-B induces an inhibition of primary root elongation. Different mutants have been isolated that are deficient in this response; however, little is known about the cellular and molecular mechanisms that regulate inhibition of root elongation in seedlings exposed to UV-B. In this work, we investigated the effect UV-B irradiation of different organs on primary root elongation. Our results demonstrate that irradiation of the leaves and shoots only induce a partial inhibition of primary root elongation, while when only roots are exposed to this radiation, primary root inhibition is similar as that measured when the complete seedling is irradiated. The consequences of exposure at different root developmental stages and times after the end of the treatment was also studied. We here show that inhibition of primary root elongation is a consequence of a decrease in cell proliferation in the meristematic zone of the primary roots, while the elongation zone size is not affected by the treatment. The decrease in cell number after UV-B exposure is partially compensated by an increase in cell length in the root meristem; however, this compensation is not enough to maintain the meristem size. We also here demonstrate that, similarly as what occurs in developing leaves, GROWTH REGULATING FACTOR 3 (GRF3) transcription factor regulates cell proliferation in UV-B irradiated roots; however, and in contrast to what occurs in the leaves, this response does not depend on the presence of MITOGEN ACTIVATED PROTEIN KINASE3 (MPK3). Inhibition of primary root elongation by UV-B under our experimental conditions is also independent of the UV-B photoreceptor UV RESISTANT LOCUS8 (UVR8) or ATAXIA TELANGIECTASIA MUTATED (ATM); but a deficiency in ATM AND RAD3-RELATED (ATR) expression increases UV-B sensitivity in the roots. Finally, our data demonstrate that UV-B affects primary root growth in various Arabidopsis accessions, showing different sensitivities to this radiation.